PENGARUH KEPEMIMPINAN ETIS DAN KOMITMEN ORGANISASIONAL TERHADAP IKLIM HUBUNGAN INDUSTRIAL YANG DIMEDIASI DARI SUARA KARYAWAN PADA KARYAWAN PT PEGADAIAN (PERSERO) KANTOR PEGADAIAN SYARIAH AREA BANDA ACEH - Muhammad Hanif; Hamdi Harmen (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2022)
Absract: This study aims to measure the Influence of Ethical Leadership and Organizational Commitment to the Climate of Industrial Relations Mediated from Employee Voices. The population used in this research is the employees of PT (PERSERO) Pegadaian Syariah Banda Aceh which consists of 95 employees. The sample used is as many as 83 people. The sampling technique used is Probability Sampling and the type of sampling is Simple Random Sampling. The data collection equipment used in this study was a questionnaire. The method used is Multiple Linear Regression is used as an analytical method to determine the effect of the dependent variable. The results of the analysis explain that there is a significant influence of Ethical Leadership on the Climate of Industrial Relations, There is no influence of Ethical Leadership on the Voice of Employees, There is no effect of Ethical Leadership on the Voice of Employees, There is an effect of Organizational Commitment on the Voice of Employees, There is an influence of the Voice of Employees on the Climate of Industrial Relations, No there is the effect of mediating variable Employee Voice of Ethical Leadership on Industrial Relations Climate. There is no mediating effect of Employee Voice from Organizational Commitment to Industrial Relations Climate on employees at PT (PERSERO) Pegadaian Syariah Banda Aceh Area